2017
DOI: 10.1038/s41598-017-16373-7
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Alleviates Oxygen–Glucose Deprivation/Reoxygenation Injury by Suppressing Endoplasmic Reticulum Calcium Release via PLC

Abstract: As documented in our previous study, notoginsenoside R1 (NGR1) can inhibit neuron apoptosis and the expression of endoplasmic reticulum (ER) stress-associated pro-apoptotic proteins in hypoxic–ischemic encephalopathy. Recent evidence indicates that the Phospholipase C (PLC)/inositol 1,4,5-trisphosphate receptor (IP3R) is important for the regulation of Ca2+ release in the ER. Ca2+ imbalance can stimulate ER stress, CAMKII, and cell apoptosis. The purpose of this study was to further investigate the neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…As mentioned above, both neuroprotective and neurotrophic functions of NGR1 were revealed. These findings were in line with a previous study, in which the neuroprotective function of NGR1 was reported in an oxygen-glucose deprivation/reoxygenation injury model [31].…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned above, both neuroprotective and neurotrophic functions of NGR1 were revealed. These findings were in line with a previous study, in which the neuroprotective function of NGR1 was reported in an oxygen-glucose deprivation/reoxygenation injury model [31].…”
Section: Discussionsupporting
confidence: 93%
“…7 NGR1 also functions as a neuroprotective effective component in alleviating oxygen-glucose deprivation/reoxygenation injury. 8 Importantly, NGR1 revealed anti-inflammatory effects in multiple situations, such as endotoxin-induced inflammatory in H9c2 cardiomyocytes, 9 oxidized low-density lipoprotein-induced inflammatory in human endothelial EA.Hy926 cells. 10 Due to its strong effects in regulating inflammatory injury, we intended to explore whether NGR1 could have effects in controlling the inflammation of burn injury.…”
Section: Introductionmentioning
confidence: 99%
“…Further study shows that NG-R1 may positively improve the binding of GRP78 to PERK and IRE1α, suppress PLC/IP3R signaling pathway, and decrease cell apoptosis in oxygenglucose deprivation/reoxygenation (OGD/R) rat model. 62 Consistently, NG-R1 protects against brain damage in OGD/ R rat model, upregulates the expression of PI3K/AKT/mTOR signaling pathway, and downregulates JNK signaling pathway by activating estrogen receptors 63 (Figure 2). NG-R1 has been demonstrated to prevent OGD/R-induced oxidative stress by inhibiting the generation of NADPH oxidase-and mitochondria-based superoxide, malondialdehyde, protein carbonyl, and 8-hydroxydeoxyguanosine in vivo and in vitro.…”
Section: Dovepressmentioning
confidence: 72%